Q fever: Evidence of a massive yet undetected cross‐border outbreak, with ongoing risk of extra mortality, in a Dutch–German border region. Issue 4 (20th February 2020) - Hackert, Volker H.; Hoebe, Christian J. P. A.; Dukers‐Muijrers, Nicole; Krafft, Thomas; Kauhl, Boris; Henning, Klaus; Karges, Wolfram; Sprague, Lisa; Neubauer, Heinrich; Al Dahouk, Sascha
Abstract: Background: Following outbreaks in other parts of the Netherlands, the Dutch border region of South Limburg experienced a large‐scale outbreak of human Q fever related to a single dairy goat farm in 2009, with surprisingly few cases reported from neighbouring German counties. Late chronic Q fever, with recent spikes of newly detected cases, is an ongoing public health concern in the Netherlands. We aimed to assess the scope and scale of any undetected cross‐border transmission to neighbouring German counties, where individuals unknowingly exposed may carry extra risk of overlooked diagnosis. Methods: (A) Seroprevalence rates in the Dutch area were estimated fitting an exponential gradient to the geographical distribution of notified acute human Q fever cases, using seroprevalence in a sample of farm township inhabitants as baseline. (B) Seroprevalence rates in 122 neighbouring German postcode areas were estimated from a sample of blood donors living in these areas and attending the regional blood donation centre in January/February 2010 ( n  = 3, 460). (C) Using multivariate linear regression, including goat and sheep densities, veterinary Q fever notifications and blood donor sampling densities as covariates, we assessed whether seroprevalence rates across the entire border region were associated with distance from the farm. Results: (A) Seroprevalence in the outbreak farm's township was 16.1%. Overall seroprevalence in the Dutch area was 3.6%. (B) Overall seroprevalence in the German area was 0.9%. Estimated mean seroprevalence rates (per 100, 000 population) declined with increasing distance from the outbreak farm (0–19 km = 2, 302, 20–39 km = 1, 122, 40–59 km = 432 and ≥60 km = 0). Decline was linear in multivariate regression using log‐transformed seroprevalence rates (0–19 km = 2.9 [95% confidence interval (CI) = 2.6 to 3.2], 20 to 39 km = 1.9 [95% CI = 1.0 to 2.8], 40–59 km = 0.6 [95% CI = −0.2 to 1.3] and ≥60 km = 0.0 [95% CI = −0.3 to 0.3]). Conclusions: Our findings were suggestive of widespread cross‐border transmission, with thousands of undetected infections, arguing for intensified cross‐border collaboration and surveillance and screening of individuals susceptible to chronic Q fever in the affected area.